2013
DOI: 10.1242/jcs.103713
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of reduced cytochrome b and mitophagy components are required to trigger nonspecific autophagy following induced mitochondrial dysfunction

Abstract: SummaryMitochondria are essential organelles producing most of the energy required for the cell. A selective autophagic process called mitophagy removes damaged mitochondria, which is critical for proper cellular homeostasis; dysfunctional mitochondria can generate excess reactive oxygen species that can further damage the organelle as well as other cellular components. Although proper cell physiology requires the maintenance of a healthy pool of mitochondria, little is known about the mechanism underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…In that work, Deffieu and co-authors found that prolonged incubation of yeast cells in the presence of the uncoupler CCCP also induced GFP-Atg8 proteolysis (Deffieu et al, 2013), although the effect was much less pronounced than in the case of treatment with myxothiazole. Uncouplers dissipate energy in mitochondria and, therefore, theoretically, can induce an unspecific starvation response, which is known to induce macroautophagy (Tal et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In that work, Deffieu and co-authors found that prolonged incubation of yeast cells in the presence of the uncoupler CCCP also induced GFP-Atg8 proteolysis (Deffieu et al, 2013), although the effect was much less pronounced than in the case of treatment with myxothiazole. Uncouplers dissipate energy in mitochondria and, therefore, theoretically, can induce an unspecific starvation response, which is known to induce macroautophagy (Tal et al, 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Inhibitors of the respiratory chain have been shown to induce bulk autophagy in yeast cells, but required the selective autophagy receptor Atg32 (Deffieu et al, 2013). In that work, Deffieu and co-authors found that prolonged incubation of yeast cells in the presence of the uncoupler CCCP also induced GFP-Atg8 proteolysis (Deffieu et al, 2013), although the effect was much less pronounced than in the case of treatment with myxothiazole.…”
Section: Discussionmentioning
confidence: 99%
“…These observations support YME1LI as a NUMT suppressor gene in humans whose inactivation leads to increased numtogenesis. Yme1 removes the damaged or dysfunctional mitochondria by mitophagy and maintains a healthy pool of mitochondria in the cell [81]. These observations implicate mitophagy in mediating accumulation and transfer of mtDNA into the nuclear genome.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have identified that inactivation of YME1L1 in colorectal tumors induces migration of mtDNA to the nuclear genome [173]. In yeast, Yme1 (yeast homolog of human YME1L1) aids in the removal of damaged mitochondria by mitophagy, a stringent mechanism that controls the quality of mitochondria and maintains a healthy pool of this organelle within the cells [174]. These observations lead us to suggest that compromised mitophagy is involved in the accumulation of mtDNA in the nucleus [174].…”
Section: Mitochondria In Intracellular Information Transfermentioning
confidence: 99%
“…In yeast, Yme1 (yeast homolog of human YME1L1) aids in the removal of damaged mitochondria by mitophagy, a stringent mechanism that controls the quality of mitochondria and maintains a healthy pool of this organelle within the cells [174]. These observations lead us to suggest that compromised mitophagy is involved in the accumulation of mtDNA in the nucleus [174]. Indeed, compromised mitophagy due to loss of Yme1 [175] or acid endonuclease DNase IIα [176] can lead to the cytoplasmic accumulation of incompletely digested mtDNA, which ultimately ends up in the nucleus.…”
Section: Mitochondria In Intracellular Information Transfermentioning
confidence: 99%